Dietary valine improved growth, immunity, enzymatic activities and expression of TOR signaling cascade genes in rainbow trout, Oncorhynchus mykiss fingerlings - Ishtiyaq Ahmad; Imtiaz Ahmed; Nazir A. Dar (Scientific Reports, 2021)
Abstract This study was conducted to determine the effects of dietary valine (Val) on growth, hemato-biochemical parameters, immunity, enzymatic activities, antioxidant status and expression of target of rapamycin (TOR) and 4E-BP genes in rainbow trout, Oncorhynchus mykiss (1.57 ± 0.03 g; 5.10 ± 0.34 cm). Six isonitrogenous (450 g kg−1) and isoenergetic (20.90 kJ 100 g−1 , gross energy) diets were designed to represent varied Val levels (10.5, 13.0, 15.5, 18.0, 20.5 and 23.0 g kg−1 dry diet basis). Growth parameters improved significantly (P < 0.05) with the amelioration of dietary Val level up to 18.0 g kg−1. Highest (P < 0.05) body protein content was noted at 18.0 g kg−1 dietary Val. Significant differences in hematological, intestinal enzymatic activities and antioxidant parameters were noted. However, plasma variables did not show any significant differences except aspartate transaminase and uric acid. Total protein content increased significantly, while the albumin and globulin content did not show any significant (P > 0.05) difference. Moreover expression of TOR mRNA and elF4E-binding protein (4E-BP) was observed higher (P < 0.05) at 18.0 g kg−1 Val. On the basis of results, optimum dietary Val requirement for maximal growth of rainbow trout was determined to be 18.19 g kg−1 of dry diet, corresponding to 40.42 g kg−1 of dietary protein.